Answer

Verified

434.1k+ views

Hint: First of all by using the formula for general terms of binomial expansion that is, \[Tn={}^{n}{{C}_{r}}{{a}^{n-r}}{{b}^{r}}\], write the general term of ${{\left( x+\dfrac{1}{x} \right)}^{4}}$by taking $a=x,b=\dfrac{1}{x}$ and n=4. Then put the power of x = 0 to find the term independent of x.

Complete step-by-step answer:

Let us consider the expression given in question as

$A={{\left( x+\dfrac{1}{x} \right)}^{4}}$…………… (1)

We know that, by binomial theorem, we can expand ${{\left( a+b \right)}^{n}}$ as,

${{\left( a+b \right)}^{n}}={}^{n}{{C}_{1}}{{a}^{n-1}}{{b}^{1}}+{}^{n}{{C}_{2}}{{a}^{n-2}}{{b}^{2}}+{}^{n}{{C}_{3}}{{a}^{n-3}}{{b}^{3}}+.......{}^{n}{{C}_{n}}{{a}^{1}}{{b}^{n-1}}$

We can also write it as,

${{\left( a+b \right)}^{n}}=\sum\limits_{r=1}^{n}{{}^{n}{{C}_{r}}}{{a}^{n-r}}{{b}^{r}}$

Therefore, we get general term in expansion of

${{\left( a+b \right)}^{n}}\ as\ {}^{n}{{C}_{r}}{{a}^{n-r}}{{b}^{r}}$

By taking $a=x,b=\dfrac{1}{x}\And n=4$we get general term of ${{\left( x+\dfrac{1}{x} \right)}^{4}}$as,

General term of ${{\left( x+\dfrac{1}{x} \right)}^{4}}={}^{4}{{C}_{r}}{{\left( x \right)}^{4-r}}{{\left( \dfrac{1}{x} \right)}^{r}}$

Let us consider this general term as,

$Tn={}^{4}{{C}_{r}}{{\left( x \right)}^{4-r}}{{\left[ \dfrac{1}{x} \right]}^{r}}$

We know that ${{\left( \dfrac{a}{b} \right)}^{n}}=\dfrac{{{a}^{n}}}{{{b}^{n}}}$ , applying this in above expression, we get,

$Tn={}^{4}{{C}_{r}}{{\left( x \right)}^{4-r}}\dfrac{{{\left( 1 \right)}^{r}}}{{{\left( x \right)}^{r}}}$

Or we get $Tn={}^{4}{{C}_{r}}{{\left( x \right)}^{4-r}}\dfrac{1}{{{\left( x \right)}^{r}}}$

We can also write above expression as,

\[Tn=\dfrac{{}^{4}{{C}_{r}}{{\left( x \right)}^{4-r}}}{{{\left( x \right)}^{r}}}\]

Now, we know that $\dfrac{{{a}^{p}}}{{{a}^{q}}}={{a}^{p-q}}$. By applying this in above expression, we get

\[Tn={}^{4}{{C}_{r}}{{\left( x \right)}^{\left( 4-r \right)-r}}\]

Therefore, we get \[Tn={}^{4}{{C}_{r}}{{\left( x \right)}^{4-2r}}\]……………. (2)

Now, to find the term which is independent of x, we must put the power of x = 0.

Therefore we get, 4-2r=0

By taking the terms containing ‘r’ to one side and constant term to other side, we get,

$\Rightarrow 2r=4$

By dividing 2 on both sides, we get,

$\begin{align}

& \Rightarrow \dfrac{2r}{2}=\dfrac{4}{2} \\

& \Rightarrow r=2 \\

\end{align}$

Now to get the term independent of x, we put r= 2 in equation (2), we get,

$\begin{align}

& Tn={}^{4}{{C}_{2}}{{\left( x \right)}^{4-2\left( 2 \right)}} \\

& Tn={}^{4}{{C}_{2}}{{x}^{4-4}} \\

& Tn={}^{4}{{C}_{2}}{{\left( x \right)}^{0}} \\

\end{align}$

We know that ${{\left( a \right)}^{0}}=1$, therefore we get.

$Tn={}^{4}{{C}_{2}}$

$\begin{align}

& Tn=\dfrac{4!}{2!2!} \\

& Tn=6 \\

\end{align}$

Therefore, we get the term independent of x in ${{\left( x+\dfrac{1}{x} \right)}^{4}}$as ${}^{4}{{C}_{2}}=6$.

Note: Students must note that when they are asked to find the term independent of variable, they should always put the power of that variable = 0. Also students must take special care while writing each term and cross check if they have written it correctly or not. Students often make mistakes while writing the powers and this must be avoided.

Complete step-by-step answer:

Let us consider the expression given in question as

$A={{\left( x+\dfrac{1}{x} \right)}^{4}}$…………… (1)

We know that, by binomial theorem, we can expand ${{\left( a+b \right)}^{n}}$ as,

${{\left( a+b \right)}^{n}}={}^{n}{{C}_{1}}{{a}^{n-1}}{{b}^{1}}+{}^{n}{{C}_{2}}{{a}^{n-2}}{{b}^{2}}+{}^{n}{{C}_{3}}{{a}^{n-3}}{{b}^{3}}+.......{}^{n}{{C}_{n}}{{a}^{1}}{{b}^{n-1}}$

We can also write it as,

${{\left( a+b \right)}^{n}}=\sum\limits_{r=1}^{n}{{}^{n}{{C}_{r}}}{{a}^{n-r}}{{b}^{r}}$

Therefore, we get general term in expansion of

${{\left( a+b \right)}^{n}}\ as\ {}^{n}{{C}_{r}}{{a}^{n-r}}{{b}^{r}}$

By taking $a=x,b=\dfrac{1}{x}\And n=4$we get general term of ${{\left( x+\dfrac{1}{x} \right)}^{4}}$as,

General term of ${{\left( x+\dfrac{1}{x} \right)}^{4}}={}^{4}{{C}_{r}}{{\left( x \right)}^{4-r}}{{\left( \dfrac{1}{x} \right)}^{r}}$

Let us consider this general term as,

$Tn={}^{4}{{C}_{r}}{{\left( x \right)}^{4-r}}{{\left[ \dfrac{1}{x} \right]}^{r}}$

We know that ${{\left( \dfrac{a}{b} \right)}^{n}}=\dfrac{{{a}^{n}}}{{{b}^{n}}}$ , applying this in above expression, we get,

$Tn={}^{4}{{C}_{r}}{{\left( x \right)}^{4-r}}\dfrac{{{\left( 1 \right)}^{r}}}{{{\left( x \right)}^{r}}}$

Or we get $Tn={}^{4}{{C}_{r}}{{\left( x \right)}^{4-r}}\dfrac{1}{{{\left( x \right)}^{r}}}$

We can also write above expression as,

\[Tn=\dfrac{{}^{4}{{C}_{r}}{{\left( x \right)}^{4-r}}}{{{\left( x \right)}^{r}}}\]

Now, we know that $\dfrac{{{a}^{p}}}{{{a}^{q}}}={{a}^{p-q}}$. By applying this in above expression, we get

\[Tn={}^{4}{{C}_{r}}{{\left( x \right)}^{\left( 4-r \right)-r}}\]

Therefore, we get \[Tn={}^{4}{{C}_{r}}{{\left( x \right)}^{4-2r}}\]……………. (2)

Now, to find the term which is independent of x, we must put the power of x = 0.

Therefore we get, 4-2r=0

By taking the terms containing ‘r’ to one side and constant term to other side, we get,

$\Rightarrow 2r=4$

By dividing 2 on both sides, we get,

$\begin{align}

& \Rightarrow \dfrac{2r}{2}=\dfrac{4}{2} \\

& \Rightarrow r=2 \\

\end{align}$

Now to get the term independent of x, we put r= 2 in equation (2), we get,

$\begin{align}

& Tn={}^{4}{{C}_{2}}{{\left( x \right)}^{4-2\left( 2 \right)}} \\

& Tn={}^{4}{{C}_{2}}{{x}^{4-4}} \\

& Tn={}^{4}{{C}_{2}}{{\left( x \right)}^{0}} \\

\end{align}$

We know that ${{\left( a \right)}^{0}}=1$, therefore we get.

$Tn={}^{4}{{C}_{2}}$

$\begin{align}

& Tn=\dfrac{4!}{2!2!} \\

& Tn=6 \\

\end{align}$

Therefore, we get the term independent of x in ${{\left( x+\dfrac{1}{x} \right)}^{4}}$as ${}^{4}{{C}_{2}}=6$.

Note: Students must note that when they are asked to find the term independent of variable, they should always put the power of that variable = 0. Also students must take special care while writing each term and cross check if they have written it correctly or not. Students often make mistakes while writing the powers and this must be avoided.

Recently Updated Pages

Three beakers labelled as A B and C each containing 25 mL of water were taken A small amount of NaOH anhydrous CuSO4 and NaCl were added to the beakers A B and C respectively It was observed that there was an increase in the temperature of the solutions contained in beakers A and B whereas in case of beaker C the temperature of the solution falls Which one of the following statements isarecorrect i In beakers A and B exothermic process has occurred ii In beakers A and B endothermic process has occurred iii In beaker C exothermic process has occurred iv In beaker C endothermic process has occurred

The branch of science which deals with nature and natural class 10 physics CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Define absolute refractive index of a medium

Find out what do the algal bloom and redtides sign class 10 biology CBSE

Prove that the function fleft x right xn is continuous class 12 maths CBSE

Trending doubts

What is BLO What is the full form of BLO class 8 social science CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE

Change the following sentences into negative and interrogative class 10 english CBSE

What organs are located on the left side of your body class 11 biology CBSE

What is pollution? How many types of pollution? Define it